Establishment of shoot multiplication system and cryopreservation of jackfruit (Artocarpus heterophyllus Lamk) shoot tips - Okunade, Oluwagade Adenike (2017)
Jackfruit produces recalcitrant seeds that are dessication-sensitive and cannot be stored by conventional seed storage. This poses a major problem for conservation of valuable genetic diversity of this plant species. Thus, sustainable conservation of its germplasm is imperative. Cryopreservation is the only viable option for long-term storage of recalcitrant plant species. The aim of this study, therefore, is to develop in vitro multiplication system using shoots obtained from seedlings and cryopreservation protocol for in vitro shoot tips. The results presented in this thesis ascertain that the physiological and developmental state of explant and suitable in vitro culture system coupled with optimization of the various steps involved in cryopreservation protocols are critical factors that influence successful cryopreservation of jackfruit shoot tips. To establish an efficient in vitro culture, suitable seeds were selected for seedling establishment. Seeds from top, middle and basal section of the fruit were extracted and germinated. The seeds from the middle and basal sections germinated earlier than those from the top and had 100% germination. In vitro culture was established using shoot tips from the germinated seedlings at 4, 6, 8 and 12 weeks with variation in terminal shoot developmental stage viz shoot with unexpanded leaf, shoot with partially expanded leaf and shoot with expanded leaf. The results showed that terminal shoot obtained from 6-week-old seedlings in MS medium supplemented with 3.0 mg/L benzylaminopurine performed best compared with 4, 8 and 12-week-old seedlings. Shoots with partially expanded leaf and with expanded leaf obtained from 6 weeks old seedlings induced 100% new shoots and produced up to seven multiple shoots than shoots with unexpanded leaf. The shoot tips form the multiple shoot produced in vitro were used to establish the cryo-protocol. Successful cryopreservation was achieved by using 6-week in vitro cultured shoot tips of sizes 1.5 mm - 2.0 mm as the explant. Two cryopreservation protocol viz vitrification and encapsulation-vitrification techniques using plant vitrification solutions: PVS2, PVS3 and PVS4 were carried out. The findings of the study on encapsulation shows that stepwise exposure to PVS2 [30% (w/v) glycerol 15% (w/v) ethylene glycol, 15% (w/v) DMSO, 0.4 M sucrose] resulted in survival of 82.1% and 23.5% in non-cryopreserved and cryopreserved encapsulated shoot tips. In contrast, survival of 88.9% and 35.2% was obtained with direct exposure to PVS3 [50% (w/v) glycerol, 50% sucrose] while PVS4 [35% (w/v) glycerol, 20% (w/v) ethylene glycol, 0.6 M sucrose] resulted in 77.1% and 37.0% survival respectively. Moreover, 28.7% survival was obtained with PVS2 at 0°C while a higher percentage survival of 35.8% and 37.9% was obtained at 25°C with PVS3 and PVS4 in cryopreserved shoot tips respectively. In non-encapsulated shoot tips, sucrose concentration at 0.5 M exposed for 48 h induced cryotolerance to dehydration. Elevated sucrose concentration (0.7 - 0.9 M) and extended period of exposure (72 - 240 h) was detrimental. The different plant vitrification solution used had varied responses on the shoot tips at different times of exposure. The critical hydration window range 49.7% - 52.4% water content was attained in all the vitrification solutions with survival range of 26.8% - 37.4% at different time of exposure. Histological observation revealed that structural changes occurred in the cell during incubation with plant vitrification solution and freezing. Sucrose preculture and PVS4 treatment for 50 minutes (52.4% WC) was able to preserved some living cells against damage during freezing. This study was successful in establishing an efficient system for in vitro shoot tip multiplication and cryopreservation protocol by vitrification using PVS4. Thus, long-term storage of explants of Artocarpus species is possible by focusing on the critical factors influencing successful cryopreservation.